Oświata żydowska w powojennej Legnicy (1945–1968) - Szczepański, Andrzej (Biuletyn Historii Wychowania, 2013)
Education in post-war Legnica (1945–1968) When the war activities came to a close, first Jews started to come into town, mainly the former prisoners from Gross-Rosen concentration camp, and then the displaced rescued in the territory of the Soviet Union. The newcomers soon opened their own educational facilities and in the school year 1946/1947 in Legnica there were: a kindergarten, a foster house, a heder, a primary school with Hebrew as the language of lecture, a kibbutz and a Hebrew primary school. The educational pluralism did not last long because from the school year 1950/1951 there remained just one state-controlled Jewish school (the other facilities had been closed). The kindergarten was the only exception and although it received the status of a public institution it preserved Jewish character until mid-50s. The subsequent years brought significant fluctuation of teachers and students as many of them left Poland in the first half of the 1950s, whereas from 1956 more newcomers arrived from the USSR. On September 1, 1959 a high-school class was launched in the local primary school. In the 1960s the emigration of Jews from Legnica increased significantly, which resulted in smaller number of students. A breakthrough year was 1968, when, because of too small number of children (38 in total), on August 31 the Jewish high-school and primary school ceased to exist